Recipe for The Global Plate: Policy Recommendation to Globalise Indonesian Culinary Arts - Kadarisman, Yusuf (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Low Indonesian culinary exports indicate that Indonesian cuisine is not well-known internationally. Culinary promotes national identity, multiethnic cultures, and tourism. On the other hand, tourism exposes local culinary practices and can become a country's international brand. Furthermore, culinary relevance to public diplomacy is recognized. Through these connections, Indonesia can utilize gastro diplomacy to capture the global culinary arts market. Indonesia can learn from Thailand and South Korea how to implement the program more effectively by using the policy transfer framework. Thailand programs addressed various elements that must be developed when opening an overseas culinary arts business. They involved governmental and non-governmental agencies because the programs are board. The South Korean program was more formalized than the Thai programs by enacting a specific law and establishing a distinct organization to oversee the program’s execution. In addition to the healthy image of South Korean cuisine and the global trend toward healthier lifestyles, South Korea's program rode the Korean pop culture wave, which set the stage for the success of the program. Based on the analysis, the recommended model for Indonesia’s program implementation consists of six components in terms of menu and target diners, regulation, responsible organizations and coordination, goals, financing sources, and personnel.